2022
DOI: 10.3390/ijerph19010549
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Labor and Burnout of Public Health Nurses during the COVID-19 Pandemic: Mediating Effects of Perceived Health Status and Perceived Organizational Support

Abstract: The purpose of this study was to identify the mediating effects of perceived health status (PHS) and perceived organizational support (POS) in the association between emotional labor and burnout in public health nurses (PHNs). The participants were 207 PHNs convenience sampled from 30 public health centers and offices in Jeju, Korea. Data regarding emotional labor, PHS, POS, and burnout were collected between February and March 2021 using a structured questionnaire. Collected data were analyzed by Pearson’s co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 39 publications
5
45
0
2
Order By: Relevance
“…With respect to the relationship between organizational support considered to be a job resource and burnout, we found its significant negative association. This finding is in line with a previous study according to which the perception of a pleasant working environment and the sense of receiving organizational care could reduce burnout among medical staff ( 50 ). Although the relationship between JD-R and burnout is well established in subject-related literature ( 22 ), most studies were conducted in the Western countries, whereas our results show that this association is consistent outside the Western context as well.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…With respect to the relationship between organizational support considered to be a job resource and burnout, we found its significant negative association. This finding is in line with a previous study according to which the perception of a pleasant working environment and the sense of receiving organizational care could reduce burnout among medical staff ( 50 ). Although the relationship between JD-R and burnout is well established in subject-related literature ( 22 ), most studies were conducted in the Western countries, whereas our results show that this association is consistent outside the Western context as well.…”
Section: Discussionsupporting
confidence: 93%
“…It is important especially in the context of COVID-19 pandemic, during which many nurses perceived their workplace as potentially harmful and dangerous. As previous studies reported, organizational support during COVID-19 pandemic was associated with lower level of anxiety ( 79 ), lower burnout occurrence ( 50 ) and increased work engagement among nurses ( 80 ). Moreover, as we showed, organizational support could reduce burnout in nurses via a decrease in surface acting.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Other studies reported the effects of work stress on nursing staff burnout (8,(11)(12)(13)(14)(15). However, only few studies investigated the effects of organizational and community support in addressing the adverse psychological effects of COVID-19, and its relationship to the coping strategies deployed by the nursing staff (16)(17)(18)(19).…”
Section: Background Frontline Nurse Challengesmentioning
confidence: 99%
“…Nurses should know and control the process required for managing their emotions and expressions [ 9 ]. Excessive emotional labor can cause mental health problems [ 10 ], musculoskeletal symptoms [ 11 ], cardiovascular disease [ 12 ], and other physical health problems [ 13 ]. Although emotional labor is an important part of nursing practice, it is usually invisible, neglected and under estimated [ 14 ].…”
Section: Introductionmentioning
confidence: 99%